Phenotypic Screen Identifies a Small Molecule Modulating ERK2 and Promoting Stem Cell Proliferation - Yin, Chang; Fufa, Temesgen; Chandrasekar, Gayathri; Aeluri, Madhu; Zaky, Verina; Abdelhady, Shaimaa; Rodríguez, Antonio B.; Jakobsson, Johan; Varnoosfaderani, Farzaneh Shahin; Mahalingam, Jayashri; Liu, Jianping; Larsson, Olle; et al. (Frontiers in Pharmacology, 2017)
Stem cells display a fundamentally different mechanism of proliferation control when compared to somatic cells. Uncovering these mechanisms would maximize the impact in drug discovery with a higher translational applicability. The unbiased approach used in phenotype-based drug discovery (PDD) programs can offer a unique opportunity to identify such novel biological phenomenon. Here, we describe an integrated phenotypic screening approach, employing a combination of in vitro and in vivo PDD models to identify a small molecule increasing stem cell proliferation. We demonstrate that a combination of both in vitro and in vivo screening models improves hit identification and reproducibility of effects across various PDD models. Using cell viability and colony size phenotype measurement we characterize the structure activity relationship of the lead molecule, and identify that the small molecule inhibits phosphorylation of ERK2 and promotes stem cell proliferation. This study demonstrates a PDD approach that employs combinatorial models to identify compounds promoting stem cell proliferation.